TEACHER COMPETENCE TEST OF ISLAMIC PRIMARY TEACHERS EDUCATION IN STATE ISLAMIC PRIMARY SCHOOLS (MIN) OF PIDIE REGENCY - Nufiar, Nufiar; Idris, Saifullah (SCAD Independent, 2016)
This study aims at examining the readiness of the Diploma-II holders of Primary Teachers Education of STIT AL-Hilal Sigli in drawing up the Lesson Plan and implementing the teaching and learning interactions in the classroom. In particular, the study attempts to figure out whether the teaching and learning interaction meet the methods listed in the Lesson Plan (RPP) and the assessment system of learner’s performance in Islamic Primary schools throughout Pidie regency. The sample of this study is nineteen Islamic Primary schools throughout Pidie regency. While to collect data from the research field, the researchers used observation, interviews, and documents. The result indicates that: (1) in general, the teachers have good and considerate preparation in drawing up the Lesson Plan within a sufficient time instead having an extemporaneous teaching. They commonly conducted the Lesson Plan preparation through the discussion with other fellow teachers which avoids them from having a significant obstacle. The only considerable stumbling blocks are the learning source, learning media, and psychological factors. All the written Lesson Plans will be accounted to the principal, superintendent, and the education department. Otherwise, the teachers will be penalized for not making one. (2) The method specified in the Lesson Plan does not correspond to the methods used in teaching and learning in general. (3) The respondents generally do not apply taxonomic Bloom in the grading system in schools where they are in charge.